A cross‐sectional study exploring cognitive impairment in kidney failure. Issue 2 (6th July 2021) - Nicholas, Pauline; Green, Theresa; Purtell, Louise; Bonner, Ann
Abstract: Background: Little is known of the prevalence or associated factors of cognitive impairment in people with kidney failure. Assessment of cognition is necessary to inform comprehension of healthcare information, aptitude for dialysis modality and informed decision making. Objectives: This study sought to determine the prevalence and factors associated with cognitive impairment in people with kidney failure. Design: Prospective cross‐sectional. Participants: Participants ( n  = 222) with chronic kidney disease grade 5 (CKD G5) including those not treated with dialysis, those undertaking dialysis independently or in a facility (CKD 5D), and those with a kidney transplant (CKD 5T). Measurements: Data were collected using the Montreal Cognitive Assessment tool, the Hospital Anxiety and Depression Scale (only the depression subscale), and a demographic questionnaire. Type of kidney disease and comorbidities were extracted from participants' hospital records. Results: Participants were 61 ± 13.63 years old; most were male (61.26%), and diabetes was the primary cause of kidney disease (34%). Prevalence of cognitive impairment was 34% although it was significantly higher for those in CKD G5 compared with other groups. A number of factors were found to be associated with cognitive impairment including, age, diabetes, hypertension, education, haemoglobin, albumin, parathyroid hormone, CKD G5, and length of time on treatment. Conclusions: Cognitive impairment in kidney failure is common and it has significant implications for informed decision making and treatment choices. Routine assessment of cognitive function is an important part of clinical practice.